Dari Pelabuhan Martapura ke Pelabuhan Trisakti: Pelayaran Perahu Rakyat Di Antara Derap Modernisasi, 1965-1995 - Susilowati, Endang (Fakultas Ilmu Budaya, Universitas Diponegoro, 2013)
The main purpose of this article is to analyze the impact of modernization that occurred in Banjarmasin port to the existence of the people shipping and how they face the challenge of modernization. The development of Trisakti port has caused a setback to the people shipping because they have to deal with the modern technology that is not likely owned by the fleet. In that case, the rational choice that they can take is adaptation and relocation. Keywords: people shipping, traditional and modern technology, adaptation, relocation.